TEACHING ENGLISH TO ADULT LEARNERS - Botirova Hakima Abduqodir qizi (Journals Park Publishing, 2023)
This paper explores the challenges and strategies involved in teaching English to adults. The demand for English language skills has increased due to globalization, immigration, and international business. Adult learners have unique needs and motivations, such as career advancement, social integration, or personal enrichment. Effective teaching approaches involve understanding their goals and preferences, assessing their level of proficiency, designing tailored activities, providing feedback and support, promoting autonomy and self-directed learning, and using authentic materials and contexts.
Keywords: adults, language, pedagogy, andragogy, ESL, recourses.